(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Under the period of the war that started in Syria in 2011, the Syrian coastal cities like Tartous received a large part of internally displaced persons. This flow of population caused a dynamic of urban and spatial suburbanization in the localities situated in suburban area. The goal of the study is to measure this dynamic between 2011 and 2019 in Tartous city and its eastern suburban area (Dwer Shekh Saad, Shekh Saad, and Bsmaqa). The study is based on various data: satellites images and population statistics. The analysis used statistic methods as (mean annual rate of expansion AUER); (Urban Growth Coefficient UGC, and Urban Expansion Differentiated Index UEDI). The main finding is that the spatial expansion was more significant in localities of the suburban area than the city because of the low cost housing. This dynamic of suburbanization is characterized by a reduction of part of population of the city in profit of the suburban area (from 92% to 83%), referring to high rate of population in the suburban area (15.5% against 3.3%). Although the AUER were high in the suburban localities, the suburbanization is characterized by densification: (UGC) is only 0.15. The study calls for stopping war in order to return internally displaced people in their safe governorates; on one hand, that will impulse a process of reconstruction; and on the other, it will reduce densification in the coastal cities and its suburban areas. This should be accompanied with durable regional and spatial planning.